Patients' Experiences in Using Diabetes Self-Management Application: A Scoping Review - Kamillah, Siti; Panduragan, Santhna Letchmi; Poddar, Sandeep; Abdullah, Bibi Florina (Kesmas, 2022)
Diabetes cases continue to increase and burden the nursing system worldwide. Diabetes Self-Management application software (DSM apps) can enable patients to manage their disease independently while simultaneously reducing the burden of the system. These apps are already available, yet global patients’ interests in using them are still low. This study aimed to describe the global tendencies of diabetes apps usage as an effort to manage diabetes cases by exploring the perceptions of diabetes patients on the use of DSM apps. This study summarized journal searches from the Elsevier, Wiley, BMC, and JMIR database with the search terms “web-based and mobile technology,” “digital health intervention,” “diabetes management mobile application,” “mobile health for diabetes self-management,” “tablet-based self-management,” and “diabetes self-management qualitative.” A total of nine journals published between January 1, 2018, to December 31, 2020, that meet the inclusion and exclusion criteria were selected. The study concludes diabetic patients in Asia, Africa, Europe, Australia, and America stated that the DSM apps used was helpful in managing diabetes. Other demographic factors such as age, level of education, and economic status have influenced the perception and tendency to use the DSM apps.